Parasitosis by Fasciola hepatica and Variations in Gut Microbiota in School-Aged Children from Peru - Silva-Caso, Wilmer (2024)
Background: Human fascioliasis is considered an endemic and hyper-endemic disease in the Peruvian Andean valleys. Our objective was to determine variations in the composition of the gut microbiota among children with Fasciola hepatica and children who do not have this parasitosis. (2) Method: A secondary analysis was performed using fecal samples stored in our biobank. The samples were collected as part of an epidemiological Fasciola hepatica cross-sectional study in children from 4 through 14 years old from a community in Cajamarca, Peru. (3) Results: In a comparison of the bacterial genera that make up the intestinal microbiota between the F. hepatica positive and negative groups, it was found that there are significant differences in the determination of Lactobacillus (p = 0.010, CI: 8.5–61.4), Bacteroides (p = 0.020, CI: 18.5–61.4), Clostridium (p < 0.001, CI: 3.5–36.0), and Bifidobacterium (p = 0.018, CI: 1.1–28.3), with each of these genera being less frequent in children parasitized with F. hepatica. (4) Conclusions: These results show that F. hepatica may be associated with direct or indirect changes in the bacterial population of the intestinal microbiota, particularly affecting three bacterial genera.